HUBUNGAN PENGETAHUAN IBU USIA REMAJA DAN DEWASA MUDA TENTANG KB DENGAN PENGGUNAAN ALAT KONTRASEPSI SETELAH MELAHIRKAN DI PUSKESMAS MABAPURA KABUPATEN HALMAHERA TIMUR - Ahmad, Sulfanawati; Hutagaol, Esther; Malara, Reginus (Universitas Sam Ratulangi, 2014)
Abstract: The success of family planning programs in Indonesia are caused by several factors, one of which factors knowledge. Purpose: to determine the relationship between knowledge teen age mothers and young adults about birth control with the use of contraceptives after childbirth. Technique: The study used a cross-sectional method, sample selection teen age mothers in total sampling and for mothers of young adults with purposive sampling. The sample of 60 respondents. The independent variable was the knowledge teen age mothers and young adults about birth control. Data was collected using a questionnaire. The data analysis using chi-square test with significance level 95% (Î± 0.05). Results: respondents with the highest yields is age teen mothers (66.7%), secondary education (43.3%), did not use birth control (68.3%), multigravida (53.4%), and lack of knowledge (65 %). The results of the statistical test p value = 1.000> Î± (0.05), then there is nothing a relationship between mother's knowledge about family planning with the use of contraceptives. Suggestion: It should further improve the quality of the health center in the provision of counseling about contraception, family planning program as well. Keywords: Knowledgemothers, contraception, childbirth Abstrak: Keberhasilan program KB di Indonesia disebabkan oleh beberapa faktor, salah satu diantaranya faktor pengetahuan. Tujuan: untuk mengetahui hubungan antara pengetahuan ibu usia remaja dan dewasa muda tentang KB dengan penggunaan alat kontrasepsi setelah melahirkan. Teknik Penelitian: Penelitian menggunakan metode cross sectional, pemilihan sampel ibu usia remaja secara total sampling dan untuk ibu dewasa muda secara purposive sampling. Jumlah sampel 60 responden. Variabel independen adalah pengetahuan ibu usia remaja dan dewasa muda tentang KB. Data dikumpulkan dengan menggunakan lembar kuesioner. Teknik analisa data menggunakan uji chi-square pada tingkat kemaknaan 95% (Î± 0,05). Hasil: responden dengan hasil tertinggi adalah ibu usia dewasa muda (66,7%), pendidikan SMP (43,3%), tidak menggunakan KB (68,3%), multigravida (53,4%), dan pengetahuan kurang (65%). Hasil uji statistik nilai p value = 1,000 > Î± (0,05), maka tidak ada hubungan antara pengetahuan ibu tentang KB dengan penggunaan alat kontrasepsi. Saran: Hendaknya pihak Puskesmas lebih meningkatkan kualitas dalam pemberian penyuluhan mengenai Program KB juga alat kontrasepsi. Kata kunci : Pengetahuan ibu, alat kontrasepsi, melahirkan